Higher Education Institutions as a Transformation Platform under the Sustainable Development Goals Framework - López López, Inés; Bote, Marcos; Rives, Longinos Marín; Bañón, Alicia Rubio (European Journal of Sustainable Development, 2019)
Previous research has highlighted the critical role of Higher Education Institutions (HEI) in promoting sustainability. In this vein, HEI, as a driving force of change, should actively participate in the diffusion and dissemination of the Sustainable Development Goals (SDGs) proposed by the United Nations. Thus, HEI must boost SDGs attainment both internally, through research, teaching, arts, and curricular programs, and externally, by providing a platform where different stakeholders such as firms, NGOs, public administrations, professional associations, trade unions… meet and create strategic alliances. A Spanish university has implemented a two-year project where different actors (faculties, students, NGO’s, private companies, public administration, professional associations, trade unions,…) are already working jointly in the pursuit of the SDGs. The aim of this project is two-fold. First, we intend to increase awareness of the SDGs among members of the university and, second, we want to exert an effective social impact by promoting intervention activities proposed by NGO’s and schools. Lectures, art exhibitions, workshops, volunteering programs,… enable tackling the SDGs in focus from different perspectives and contribute to their achievement. As a result, we expect more favorable attitudes towards the SDGs and a behavioral change among university members and citizens in general. Keywords: Sustainable Development Goals, Higher Education Institutions, multi-stakeholders partnership, transformation platform